Expert opinions on informational and supportive needs and sources of obtaining information in patients with inflammatory bowel disease: a Delphi consensus study - Norouzkhani, Narges; Bahari, Ali; Shirvani, Javad Shokri; Faramarzi, Mahbobeh; Eslami, Saeid; Tabesh, Hamed (Frontiers in Psychology, 2023)
Background: The present study introduces informational and supportive needs and sources of obtaining information in patients with inflammatory bowel disease (IBD) through a three-round Expert Delphi Consensus Opinions.Methods: According to our previous scoping review, important items in the area of informational and supportive needs and sources of obtaining information were elucidated. After omitting duplicates, 56 items in informational needs, 36 items in supportive needs, and 36 items in sources of obtaining information were retrieved. Both open and close questions were designed for each category in the form of three questionnaires. The questionnaires were sent to selected experts from different specialties. Experts responded to the questions in the first round. Based on the feedback, questions were modified, and sent it back to the experts in the 2 nd round. This procedure was repeated up to the 3 rd round.In the first round, five items from informational needs, one item from supportive needs, and seven items from sources of obtaining information were identified as unimportant ones and omitted. Also, two extra items were proposed by the experts, which was added to the informational needs category. In the 2 nd round, seven, three, and seven items from informational needs, supportive needs, and sources of obtaining information were omitted respectively due to unimportant . In the 3 rd round, all the included items gained scores of equal or more than the average, and were identified as the important ones. The Kendall coefficient was calculated to be 0.344 for information needs, 0.330 for supportive needs, and 0.325 for information sources, which means there were about 34%, 33%, and 32% convergence between the experts' viewpoints, respectively.Conclusions: Out of 128 items in the first round, omission of 30 items and addition of two items generated a 100-item questionnaire for three sections of informational needs, supportive needs, and sources of obtaining information with a high level of convergence between experts' viewpoints.